The Evolution of Community Policing in Chatham-Kent: Citizen Engagement, Organizational Change, and the Neighbourhood Policing Project - Poole, Dennis (2006)
This paper examines the factors that contribute to the successful implementation of community policing based on a case study of the neighbourhood policing program in Chatham-Kent. The findings reveal that police need to describe their mission in terms of crime prevention, fear reduction, and crime control and neighbourhood police officers can effectively address the local circumstances that lead to crime and disorder depending on the willingness of citizens to help them detect and solve crimes